Age‐associated variation in the gut microbiota of chinstrap penguins (Pygoscelis antarctica) reveals differences in food metabolism. Issue 2 (7th May 2021) - Tian, Jiashen; Du, Jing; Zhang, Shengjiu; Li, Yanqiu; Gao, Xianggang; Han, Jiabo; Lu, Zhichuang
Abstract: Age is known to affect the gut microbiota in various animals; however, this relationship is poorly understood in seabirds. We investigated the temporal succession of gut microbiota in captive chinstrap penguins of different ages using high‐throughput sequencing. The gut microbiota exhibited a significant age succession pattern, reaching maturity in adults and then declining with increasing age. Only 15 amplicon sequence variants were shared among the gut microbiota in chinstrap penguins at all studied ages, and these contributed to most of the age‐related variations in total gut microbiota. Co‐occurrence networks found that these key bacteria belonged to the genera Acinetobacter, Clostridium sensu stricto, and Fusobacterium, and more species interactions were found within the same taxonomy. Functional prediction indicated that most of the metabolic functions were more abundant in the gut microbiota in adult chinstrap penguins, except for carbohydrate metabolism, which was significantly more abundant in older individuals. Abstract : The gut microbiota of chinstrap penguins exhibited a significant age succession pattern, reaching maturity in adults and then declining with increasing age. Only 15 bacterial strains were shared among the gut microbiota in chinstrap penguins at all studied ages, and these contributed to most of the age‐related variations in total gut microbiota. Most of the metabolic functions were more abundant in the gut microbiota of adult chinstrap penguins, except for carbohydrate metabolism, which was more abundant in older individuals. ​